Implikasi Klausula Baku terhadap Perlindungan Konsumen dalam Pengembalian Barang - Rizki Ihdan Maulana; Teddy Prima Anggriawan (CV Rewang Rencang, 2025)
Legal protection for consumers harmed by standard clauses in e-commerce, particularly regarding returns, has become a crucial issue with the rise in online sales transactions. Standard clauses are often unilaterally included by businesses and often limit or eliminate consumers' right to return goods if the product received is not suitable or damaged. This contradictory practice is based on consumer protection principles stipulated in the Consumer Protection Law (UUPK), specifically Article 18, which prohibits the inclusion of standard clauses because they can eliminate consumers' right to return goods.